On household living conditions. A comparison between capital agglomerations and their popular neighborhoods in Northwestern Argentina. - Batista-Zamora, Ana Ester; Natera-Rivas, Juan José (Nicolaus Copernicus University. Torun. Polonia., 2023)
Access to basic facilities such as electricity, running water or sewerage is not homogeneous among households in the provincial capitals of Northwestern Argentina. Th rough the use of the National Registry of Popular Neighborhoods and by calculating a Housing Suffi ciency Index, we carried out a gradation in the levels of access to these basic facilities by households residing in these popular neighborhoods, identifying in which agglomeration the situation is more positive and in which the opposite situation is recorded. At the same time, using statistics from the Permanent Household Survey, we carried out the same procedure, but applied to the total number of households in each agglomeration. Th e comparison of both gradations shows signifi cant diff erences in some of the capital cities, which refl ects the existing urban fragmentation.
Keywords: Infraestructura (Economía); Noroeste de Argentina - Población; RENABAP; Northwest Argentina; Basic services; Households